Konsep Ma’rifat Dalam Serat Wirid Hidayat Jati Karya Ronggowarsito - Nurul Istiqomah; Wahyudin Darmalaksana; Naan Naan (Syifa al-Qulub, 2021)
This study aims to analyze the concept of Ma'rifat in Serat Wirid Hidayat Jati Ronggowarsito. This study uses a qualitative method that applies the object of literature research which is categorized as library research. The results and discussion of this study include the conceptualization of Ma'rifat in Sufism, Ronggowarsito biography and Serat Wirid Hidayat Jati and Ma'rifat in Serat Wirid Hidayat Jati. The conclusion in this study is that Serat Wirid Hidayat Jati as a monumental work of a Javanese Sufi, namely Ronggowarsito, contains descriptions of Ma'rifat teachings which have implications for wisdom which includes good deeds in life. This study recommends further research with a holistic perspective.